Socio-economic evaluation of the national integrated pest management (IPM) programme for rice in Uttar Pradesh - Mishra, B. K. (Allahabad : Agro-Economic Research Centre, University of Allahabad, 2000)
With special reference to Ghazipur and Udham Singh Nagar Districts, Uttar Pradesh.
Includes statistical tables.
Keywords: Pests -- Control; Pests -- Control